Pelatihan Mendesain Pembelajaran Inovatif bagi Guru SMP Negeri 6 Garut: Innovative Learning Design Training for Teachers of SMP Negeri 6 Garut - Nasution, Syaiful Hamzah; Jupri, Al; Darhim, Darhim; Pratama, Elvandri Yogi; Astiswijaya, Nike; Fajriadi, Dede; Zakiah, Nur Eva; Masitoh, Lisda Fitriana; Prasetyawan, Enggar; Wijayanti, Palupi Sri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
In this era of globalization, there are many developments and reforms in the field of education. The demands of 21st-century skills encourage teachers to innovate in learning. This aims to provide the best service for students and also as an effort to optimize the potential possessed by students. For this reason, teachers at SMP Negeri 6 Garut tried to improve their knowledge and insights about innovative learning. This community service aims to provide training on how to design innovative learning for teachers at SMP Negeri 6 Garut. Implementing this community service activity uses lecture and practice methods using concrete and interactive learning media (ICT-based). The service team visiting SMP Negeri 6 Garut carried out the lecture method, which provided material on innovative learning and the use of technology in learning. This community service results in teachers at SMP Negeri 6 Garut understanding the concept of innovative learning and making innovations in learning.